2014
DOI: 10.1116/1.4865903
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature CVD of iron, cobalt, and nickel nitride thin films from bis[di(tert-butyl)amido]metal(II) precursors and ammonia

Abstract: Thin films of late transition metal nitrides (where the metal is iron, cobalt, or nickel) are grown by low-pressure metalorganic chemical vapor deposition from bis[di(tert-butyl)amido]metal(II) precursors and ammonia. These metal nitrides are known to have useful mechanical and magnetic properties, but there are few thin film growth techniques to produce them based on a single precursor family. The authors report the deposition of metal nitride thin films below 300 °C from three recently synthesized M[N(t-Bu)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…No distinct signals of a Ni–N bond were detected, suggesting that the film has the structure of an interstitial compound where the nitrogen atoms occupy specific interstitial sites in the Ni metal host. Similar spectra have been shown for CVD Ni x N and for ALD Ni deposited with NH 3 plasma . The measured Ni 2p peak overlapped almost completely with a Ni metal reference.…”
Section: Resultssupporting
confidence: 79%
“…No distinct signals of a Ni–N bond were detected, suggesting that the film has the structure of an interstitial compound where the nitrogen atoms occupy specific interstitial sites in the Ni metal host. Similar spectra have been shown for CVD Ni x N and for ALD Ni deposited with NH 3 plasma . The measured Ni 2p peak overlapped almost completely with a Ni metal reference.…”
Section: Resultssupporting
confidence: 79%
“…The predominance of Ni <1+ in Ni 3 N 1− x /NF suggested that the electron density of a considerable fraction of Ni atoms was affected by the existence of nitrogen vacancies. Moreover, the peak at 398.0 eV ascribed to the NNi bonding was observed for both Ni 3 N/NF and Ni 3 N 1− x /NF in the high‐resolution N 1s XPS spectra (Figure b), and a peak centered at around 399.9 eV (denoted as V N ) was also revealed for Ni 3 N 1− x /NF. The observation of this extra peak at higher binding energy suggested the reduction of negative charges of nitrogen atoms and further verified the formation of nitrogen vacancies in Ni 3 N 1− x /NF, similar to the variation of XPS signals of oxygen in the oxide nanomaterials with oxygen vacancies .…”
mentioning
confidence: 88%
“…The synthesis of strontium N,N-dimethylaminodiboranate (DMADB) complexes with other coordinated Lewis bases can be achieved by treating the thf adduct 3 with either a stoichiometric amount or an excess of the desired Lewis base. Thus, adding 1,2-dimethoxyethane (dme), bis(2-methoxyethyl) ether (diglyme), or N,N,N′,N′-tetramethylethylenediamine (tmeda) to 3 in thf affords the new compounds Sr-(H 3 BNMe 2 BH 3 ) 2 (dme) 2 (4), Sr(H 3 BNMe 2 BH 3 ) 2 (diglyme) (5), and Sr(H 3 BNMe 2 BH 3 ) 2 (tmeda) (6), respectively, in greater than 60% yields.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Binary and higher oxides of the alkaline-earth (group 2) metals have many technological uses, both as bulk materials and as thin films. For example, strontium is a key component in advanced materials such as high-temperature superconductors, dielectrics and ferroelectrics, nonlinear optical materials, and colossal magnetoresistive materials. Thin films of these materials can generally be deposited by physical vapor deposition (PVD) methods such as sputtering, but these methods have some limitations. For example, PVD has difficulty coating or filling deeply recessed features uniformly, which is one of the process requirements in the fabrication of certain microelectronic circuit elements such as interconnects and trench capacitors. This drawback arises because PVD generates atomic species with high sticking coefficients, which form a film as soon as they encounter the surface, thus giving “line of sight” coatings. , Chemical vapor deposition (CVD), on the other hand, can provide uniform coatings even in recessed features with high aspect ratios because the molecular precursors used in CVD can undergo many adsorption/desorption events before they react to form a film …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation